Reducing deforestation through value chain interventions in countries emerging from conflict: The case of the Colombian cocoa sector. (October 2020) - Castro-Nunez, Augusto; Charry, Andres; Castro-Llanos, Fabio; Sylvester, Janelle; Bax, Vincent
Abstract: Sustainability commitments by private sector actors are emerging as interventions to help reduce global deforestation. Much attention is placed on the forest conservation impact of these interventions in areas where commodity production constitutes a main driver of deforestation. It is, however, less clearly understood what role they could play in areas where the production of commodities is not evidently leading to the loss of forest and how they could contribute to other objectives including sustainable rural development and peacebuilding. In this paper, we examine the potential of the cocoa sector in Colombia in achieving deforestation reduction and peacebuilding simultaneously, as aimed by the country's Cocoa, Forests and Peace Initiative. Results from correlations and spatially explicit analyses show that regardless of its widespread production across Colombia, in the past fifteen years cocoa has not been an important driver of deforestation. This suggests that efforts to end deforestation in the Colombian cocoa sector emerged following global trends, and not because of an evident link between cocoa production and deforestation. Furthermore, results from spatial clustering analyses highlight areas where different types of value chain interventions may be appropriate to parallel forest conservation and peacebuilding, while interviews with key actors in the cocoa sector provide clues as to how these interventions should be developed and implemented. Specifically, our results show that narratives around approaches to achieve zero deforestation from agricultural commodities should (1) be adjusted to local contexts, (2) incorporate location-specific development needs, (3) complement existing rural development efforts, (4) enhance collaboration among actors that operate both within and beyond the value chain, and (5) apply high-resolution data to assess deforestation-commodity relations and verify zero-deforestation commitments. These considerations are particularly relevant in contexts where commodity production is not evidently leading to deforestation, as in the case of cocoa production in Colombia. Highlights: We explore the role of value chain interventions (VCI) in reducing deforestation. We use quantitative analyses and interviews with key stakeholders in the cocoa sector. Results suggest that cocoa production has not led to deforestation in Colombia. VCI provide an opportunity to put private sector's zero-deforestation commitments into action. There is no conceptual frameworks to integrate deforestation concerns into VCI.